Peningkatan Kemajuan Pendidikan Melalui Ekonomi Syariah Berbasis Wakaf dan Zakat - Nely Rohmatillah (DIMENSI - Jurnal Sosiologi, 2023)
This article aims to explore the potential of Sharia-based economy through waqf and zakat in advancing education. The Sharia-based economy emphasizes Islamic values, particularly principles of social solidarity and justice, which can support the development of a more inclusive and sustainable education system. This research employs a qualitative method with a literature review approach. Through a review of previous literature, we gain an understanding of the basic concepts of Sharia-based economy, waqf, zakat, as well as challenges and opportunities in the education sector. The findings indicate that waqf and zakat can be integrated into the education system to provide long-term benefits. In the context of waqf, charitable contributions can be utilized to build educational infrastructure and facilities, provide scholarships, and support research and curriculum development. Meanwhile, zakat, as a religious obligation imposed on individuals who reach the nisab (minimum threshold) of wealth, can be directed towards educational assistance programs for underprivileged and marginalized families. In conclusion, the Sharia-based economy through waqf and zakat holds significant potential in advancing education in an inclusive and sustainable manner. Through collaborative efforts from various stakeholders and strengthening institutional capacity, the utilization of zakat and waqf in the education sector can contribute significantly to the improvement of education in different countries.